2016
DOI: 10.2147/opth.s120267
|View full text |Cite
|
Sign up to set email alerts
|

Refractive and visual outcomes after Keraring intrastromal corneal ring segment implantation for keratoconus assisted by femtosecond laser at 6 months follow-up

Abstract: PurposeWe attempted to evaluate the efficacy of femtosecond laser-assisted intrastromal corneal ring segment implantation in patients with keratoconus (KC).Patients and methodsA retrospective interventional consecutive clinical study was conducted on patients with KC who were treated with femtosecond laser Keraring implantation. All procedures were performed at Ebsar Eye Center in the period from January 5, 2015, to February 28, 2016.ResultsThirty eyes of 20 patients were included in this study. The mean age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…To avoid melting, they repositioned the migrated segment away from the incision site with successful outcomes in all of the eyes. Heikal et al reported no complications or need for ring repositioning in a 6-month follow-up of 20 patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid melting, they repositioned the migrated segment away from the incision site with successful outcomes in all of the eyes. Heikal et al reported no complications or need for ring repositioning in a 6-month follow-up of 20 patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, significant central corneal flattening, reduction of magnitude of astigmatism and improvement of CDVA were observed, with 52.8% of eyes showing a reduction in the magnitude of anterior corneal astigmatism of 1 D or more. Heikal et al [ 28 ] found in a sample of 20 adult keratoconus eyes implanted with KeraRing using the femtosecond laser technology that mean LogMAR CDVA improved from 0.85 ± 0.17 preoperatively to 0.26 ± 0.11 at 3 months postoperatively ( p = 0.001). Alfonso et al [ 13 ] reported in a sample of 118 eyes of 88 children a change of mean CDVA from 0.67 ± 0.37 logMAR preoperatively to a value of 0.37 ± 0.30 logMAR at 6 months after ICRS implantation.…”
Section: Discussionmentioning
confidence: 99%
“…ICRS implantation is a safe and reversible technique that can achieve corneal flattening and improved visual outcomes. Several factors such as the type of ICRS, the insertion technique, and patient selection contribute to the final outcome [ 28 ].…”
Section: Current Treatment Options and Managementmentioning
confidence: 99%